STUDY OF CO-MORBIDITIES AND OUTCOME IN HOSPITALISED CHILDREN WITH PRIMARY SEVERE ACUTE MALNUTRITION - Gobinda Hembram; Satyaranjan Mallick; Sangeeta Das; Mangal Charan Murmu (Student's Journal of Health Research Africa, 2023)
Introduction: Aim & Objectives: To determine the different co-morbidities associated in children aged 6 - 59 months with primary severe acute malnutrition and the outcome of primary severe acute malnutrition in children. Material & Method: This study was conducted over 2 years (From November 2019 to October 2021) at the Department of Pediatrics, S.C.B. Medical College & Hospital, S.V.P. Postgraduate Institute of Pediatrics, and Nutritional Rehabilitation Centre (NRC), Cuttack. This is a hospital-based descriptive survey study. The children aged 6 – 59 months, meeting the WHO definition of Severe Acute Malnutrition were included in the study. Results The most common presenting complaint seen in our study population was fever, present in 60 of cases. The 2nd most common presenting complaint was cough and cold in 51 (%) of subjects, followed by loose stool, seen in 34 cases; and not gaining weight in 31 (%) cases. Acute respiratory tract infections were found to be the most common infectious co-morbidity, present in 43 children. Diarrhea was the second most common infectious co-morbidity which was seen in 34 children. Conclusion: SAM is more seen in low socio-economic groups; and in families with lower rates of access to and utilization of safe water and sanitation facilities. Lower rate of complete immunization, as compared to national and state level statistics; and inadequate exclusive breastfeeding and delayed weaning are common findings in SAM children. Recommendation Exclusive breastfeeding for the first 6 months of life, followed by the introduction of complementary feeds at 6 months; continued breastfeeding till 2 years. Immunization as per schedule, as several cases were partially immunized. Socioeconomic status has to be improved including parental education regarding following hygienic practices, usage of safe water, and sanitation